The prevalence of metabolic syndrome in postmenopausal women: A systematic review and meta-analysis in Iran. Issue 6 (November 2018) - Ebtekar, Fariba; Dalvand, Sahar; Gheshlagh, Reza Ghanei
Abstract: Metabolic syndrome is a set of cardiovascular risk factors that increase the risk of cardiovascular disease, diabetes and mortality. Women are at risk of developing metabolic syndrome as they enter the postmenopausal period. The present systematic review and meta-analysis was conducted to estimate the prevalence of metabolic syndrome in Iranian postmenopausal women. In this systematic review and meta-analysis, 16 national articles published in Persian and English were gathered without time limit. National databases such as SIDs, IranMedex and MagIran, and international databases such as Web of Science, Google Scholar, PubMed and Scopus were used to search the relevant studies. We searched for articles using the keywords "menopause", "postmenopausal", "metabolic syndrome", "MetSyn", and their combinations. Data were analyzed using the meta-analysis method and the random effects model. Analysis of 16 selected articles with a sample size of 5893 people showed that the prevalence of metabolic syndrome in Iranian postmenopausal women was 51.6% (95% CI: 43–60). The prevalence of metabolic syndrome based on ATP III and IDF criteria was 54% (95% CI: 59–63) and 50% (95% CI: 45–56), respectively. Based on the results of univariate meta-regression analysis, the increase in the mean age of postmenopausal women (p = 0.001) and sample size (p = 0.029), the prevalence of metabolic syndrome increased significantly. More than half of postmenopausal women in Iran suffer from metabolic syndrome. Providing training programs for postmenopausal women to prevent and control cardiovascular disease and its complications seems to be necessary.